Targeting HGF/c-MET signaling to regulate the tumor microenvironment: Implications for counteracting tumor immune evasion - Yang Xia; Chunye Huang; Min Zhong; Hongguang Zhong; Ruiwen Ruan; Jianping Xiong; Yangyang Yao; Jing Zhou; Jun Deng (Cell Communication and Signaling)
Abstract The hepatocyte growth factor (HGF) along with its receptor (c-MET) are crucial in preserving standard cellular physiological activities, and imbalances in the c-MET signaling pathway can lead to the development and advancement of tumors. It has been extensively demonstrated that immune checkpoint inhibitors (ICIs) can result in prolonged remission in certain patients. Nevertheless, numerous preclinical studies have shown that MET imbalance hinders the effectiveness of anti-PD-1/PD-L1 treatments through various mechanisms. Consequently, clarifying the link between the c-MET signaling pathway and the tumor microenvironment (TME), as well as uncovering the effects of anti-MET treatment on ICI therapy, is crucial for enhancing the outlook for tumor patients. In this review, we examine the impact of abnormal activation of the HGF/c-MET signaling pathway on the control of the TME and the processes governing PD-L1 expression in cancer cells. The review thoroughly examines both clinical and practical evidence regarding the use of c-MET inhibitors alongside PD-1/PD-L1 inhibitors, emphasizing that focusing on c-MET with immunotherapy enhances the effectiveness of treating MET tumors exhibiting elevated PD-L1 expression.